Pemberdayaan Lansia Melalui Program Hari Lanjut Usia Nasional (HLUN) 2026 Menuju Desa Palipi Soreang Ramah Lansia di Kabupaten Majene - Fredy Akbar K; Nurul Aeni; Nur Aisyah; Syamsidar Syamsidar (STIKES Marendeng Majene, 2026)
The increasing number of older adults is an indicator of successful health development but also presents challenges related to physical, psychological, social, and functional health. Palipi Soreang Village, Majene Regency, has a relatively large older population with various health and psychosocial problems requiring continuous attention. This community service program aimed to improve the quality of life of older adults through the 2026 National Elderly Day Program toward an Age-Friendly Palipi Soreang Village. The program was conducted from June 2 – 11, 2026, involving 64 undergraduate nursing students from STIKES Marendeng Majene and targeting 103 older adults and 30 caregivers. Activities included health assessments using the Geriatric Depression Scale (GDS), body mass index (BMI), blood pressure measurement, fall-risk assessment, loneliness assessment, and cognitive function screening, as well as health education, group activity therapy, Psychological First Aid training for caregivers, a marketplace featuring older adults’ products, stakeholder advocacy, the declaration of an Age-Friendly Village, and the launch of the Palipi Soreang Elderly School. The assessment showed that 54.4% of participants were female, 75.7% were independent in daily activities, 81.6% experienced moderate loneliness, and 69.9% had no fall risk. The program increased older adults’ participation in health and social activities, strengthened caregivers’ capacity to support older adults’ mental health, and fostered cross-sectoral commitment through the Age-Friendly Village Declaration and establishment of the Palipi Soreang Elderly School. A collaborative, community-based approach can support the development of healthy, active, productive, and dignified older adults.